Leadership Styles and Competitive Advantage: Does Employee Creativity Mediate The Relationship - Almheiri, Murshid Mohamed Obaid; Romle, Abd Rahim; Omar, Rusdi (South Asian Journal of Social Sciences and Humanities, 2022)
Competitive advantage is considered as an element which is critical to achieve. This study argued that employee creativity is important for gaining competitive advantage. Likewise. the study also argued that leadership behavior play a significant role in developing creativity among employees. For the purpose of colleting the data three leadership behaviors which are supported by the literature in incorporating employee creativity for gaining competitive advantage have been chosen. The data for transformational leadership, transactional leadership, and autocratic leadership has been collected from the prior studies. The reliability and validity of the instrument has also been ensured and the data has been collected from department of Government housing programs in Abu Dhabi, Dubai, and Sharjah – UAE. The results of partial least square, structural equation modeling revealed that transformational leadership, transactional leadership, and autocratic leadership has a direct and significant positive impact over employee creativity as well as competitive advantage. The findings further ensured that employee creativity mediates the relationship between transformational leadership, transactional leadership, and autocratic leadership and competitive advantage. The findings have practical as well as theoretical significance. At the end some limitations and future recommendations are also mentioned.
Keywords: transformational leadership; transactional leadership; and autocratic leadership; competitive advantage